Cancer risk perception in relation to associated symptoms in Barrett's patients: A cross sectional study on quality of life. Issue 9 (1st November 2018) - van der Ende-van Loon, Mirjam CM; Rosmolen, Wilda D; Houterman, Saskia; Schoon, Erik J; Curvers, Wouter L
Abstract : Background: Barrett's oesophagus affects patients' quality of life and may be a psychological burden due to the threat of developing an oesophageal adenocarcinoma. Objective: Assessing the oesophageal adenocarcinoma risk perceived by non‐dysplastic Barrett's oesophagus patients and its association with quality of life, illness perception and reflux symptoms. Methods: This cross‐sectional questionnaire study included 158 Barrett's oesophagus non‐dysplastic patients aged 18–75 years. Based on their annual and lifetime oesophageal adenocarcinoma risk estimations measured with the Magnifier Scale, patients were classified as overestimating or underestimating. Associations between the groups where assed on demographics, reflux symptoms and results of the Outcomes Study Short‐Form‐36 (SF‐36) and the Brief Illness Perception Questionnaire (B‐IPQ). Results: The annual oesophageal adenocarcinoma risk was overestimated by 41%. Overestimating patients had lower means on the SF‐36 domains: bodily pain (annual p = 0.007 and lifetime p = 0.014), general health (annual p = 0.011 and lifetime p = 0.014), vitality (annual p = 0.030), physical functioning (lifetime p = 0.028), worse illness perception (total score p = 0.001) and significantly more reflux symptoms. Conclusions: Overestimation of the oesophageal adenocarcinoma risk by Barrett's oesophagus patients was associated with decreased quality of life and worse illness perceptions, which is most likely caused by symptoms of dyspepsia and reflux. These symptoms should be adequately treated, and patients may be in need of extra support and specific information about their oesophageal adenocarcinoma risk.